The relationship components of communication competence in the direct selling process in Malaysia - Nuredayu Omar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The key purpose of this paper is to explore the nature of communication competence in the direct selling context by investigating the case of direct sellers in Malaysia. The growth in direct selling worldwide has a large influence in Malaysia. In 2016, more than 3.9 million people were involved as direct sellers and 62% of these were women. This phenomenon requires a better understanding of direct selling as a communication process. For this study, eleven informants were selected from different environments of the direct selling business. This design can incorporate a diversity of direct selling context. This research employed observations and interviews to explore what constitutes communication competence in the Malaysian direct selling process by taking direct sellers conceptions of their work as the point of face-to-face interaction with potential buyers. This study found that the relationship components of communication competence play an important role in the direct selling process. Friendly attitude, similarities, and fairly calm were among the ten relationship components that have been identified in this study. Obviously, the relationship components emerged in the five direct selling communication phases namely as the preparation phase, initial meeting phase, meeting phase, closing phase, and the communication disruption. This study advocated that direct sellers should attain to communicate competently in order to develop new relationships with their potential buyers.